The Results of Health Economic Policy on Cultural Health Tourism in COVID-19 Situation Under Public Health Measures: A Case Study of a Sandbox in Chiang Khan, Loei Province - Kaewsa, Watcharee; Khawda, Nanthagan; Saenluanginn, Jitpinan; Boonkiattiboot, Rattiya (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2023)
This research explores the implementation of health economic policies in the context of health and cultural tourism during the COVID-19 pandemic, focusing on the Chiang Khan Sandbox in Loei Province. The study utilized mixed methods, combining quantitative and qualitative data collected through questionnaires and semi-structured interviews. An explanatory approach, using summary data from four articles, was employed to discuss the study's results. The participants included 661 individuals, comprising administrators, workers, business entrepreneurs, and both Thai and foreign tourists in Chiang Khan District, Loei Province. Descriptive statistics were applied to analyze quantitative data, while content analysis was used for qualitative data. The results indicated that the PDCA processes model facilitated rapid and efficient development of operations, enabling planning, implementation, evaluation, and improvement to achieve goals. Assessment using the CIPPIEST guideline, a theory by Daniel, helped identify and address problems effectively. Evaluating attitudes and participation provided insights into business operators' perspectives, contributing to goal achievement. The lessons learned from summarizing the operation's results suggested valuable insights for developing plans to handle future outbreaks. In conclusion, the operation successfully met its objectives. Additionally, the economic and tourism aspects of the community experienced recovery, making it a potential model for mitigating the impacts of pandemic diseases on both the economy and human life.